Does Service Marketing Enhance Supplier and Customer Contact in the Gig Economy Era? Case Analysis from Malaysian SMEs` Women Entrepreneurs - Filzah Md Isa; Mathivannan Jaganathan; Vincent Yeow Cher Sern; Muhd Afiq Syazwan Ahmdon; Siti Noratisah Mohd Nafi (International Journal of Supply Chain Management, 2020)
This research explores the effectiveness of service marketing strategies among Malay women entrepreneurs and how this service marketing strategy affects business performance. The study employs a qualitative method by interviewing a women entrepreneur and their strategies to compete in the market. However, with the right strategy, it is also a time full of opportunities for entrepreneurs. Descriptive statistics and interviews were used to analyse the data. The finding of this research revealed the significant role of information and communication technology (ICT) and social media in their service marketing effectiveness. Online business and social media have brought a significant improvement in the net income of these entrepreneurs, some by manifold. Therefore, women entrepreneurs must adapt to the use of ICT and social media in order to improve the sustainability of their businesses, as well as to attract the younger generation.